Locally Advanced Pancreatic Cancer: Neoadjuvant Therapy With Folfirinox Results in Resectability in 60% of the Patients. Issue 3 (September 2016) - Hackert, Thilo; Sachsenmaier, Milena; Hinz, Ulf; Schneider, Lutz; Michalski, Christoph W.; Springfeld, Christoph; Strobel, Oliver; Jäger, Dirk; Ulrich, Alexis; Büchler, Markus W.
Abstract : Objective: For patients with locally advanced and unresectable pancreatic cancer (PDAC), neodadjuvant treatment and consecutive surgical exploration have been studied during the last decade with various neoadjuvant therapies including chemotherapy and combinations with radiation. Aim of the study was the evaluation of neoadjuvant therapy with a focus on Folfirinox. Methods: All consecutive patients undergoing surgery for PDAC after neoadjuvant treatment were analyzed (clinico-pathological characteristics, secondary resection rates, outcome). Patients receiving Folfirinox were compared with other treatment regimens. Results: Between December 2001 and June 2015, 575 patients received neoadjuvant treatment and were scheduled for resection after re-staging. A successful resection was achieved in 292 patients (50.8%). Resection rates following Folfirinox were 61% (76/125 patients) compared with 46% (150/322 patients) after gemcitabine and radiation, and 52% (66/128 patients) after other treatments ( P = 0.026). Median overall survival was 15.3 months after resection vs 8.5 months after exploration alone ( P < 0.0001). Subgroup median survival was 16.0 months (Folfirinox) vs 16.5 months (gemcitabine) and 14.5 months (others) with 3-year survival of 28.1%, 23.2%, and 19.7%, respectively ( P = 0.8582). By multivariable analysis, Folfirinox was confirmed to be independently associated with a favorable prognosis. Conclusions: Folfirinox is a valuable treatment option in the neoadjuvant therapy of PDAC. From the present data, which represent the largest available study population to date, Folfirinox seems to be the most effective protocol resulting in a significantly better secondary resection rate and overall survival than other treatments. It should be considered in all patients fit for this regimen and consecutive surgical exploration.